Multilateral Global Airline Alliances and The Stock Market Reactions - Chong, Yuet Yeong (2008)
The inauguration of the three multilateral global airline alliances namely Star AllianceTM, oneworld®, and SkyTeam® had changed the nature of competition in the airline industry from competition between airlines to competition between alliances. Collectively, the three alliances generated 55 percent of the world’s passenger traffic. Despite the prevalence of these alliance groups, no stock market reactions study had been done on them thus far. Using the event study methodology, this study analyses the reactions of the stock market to announcements of airlines form, join and withdraw from these alliances. The study is done from the points of two parties, namely the announcing airlines and the existing member airlines. The study covers an initial sample of all existing and former members of these alliances during the period from 1997 to 2007, which make up to 51 airlines from 36 countries. This entails a multi country event study being conducted, differs from the general single country event studies. In addition, in order to examine the stock price implications of the existing member airlines, an equally weighted average “airline alliance index” is thus created for each of the alliances. It is found that the announcements by airlines confirm to found and join the airline alliances produced significant positive abnormal returns for the announcing airlines. This supports the general argument that alliances do create value for allied firms. However, the same announcement that new member joining an alliance had rendered negative, though insignificant, abnormal returns to the existing member airlines. This leads to the argument that positive abnormal returns enjoyed by the announcing airlines that will join the alliance are merely an appropriation of value from the existing member airlines, contrasting the general believe that alliance do create value for allied firms. The argument of alliance creates value versus appropriate value is inconclusive and hence warrant for further research. Lastly, withdrawn airlines did suffer negative abnormal returns while the existing member airlines enjoyed positive abnormal returns upon the relevant airlines withdrawal. As the withdrawn airlines under study are those with financial problems or non cooperative ones, the relevant alliance would be better off after their departure where remaining member airlines could cooperate more effectively. As a result, positive abnormal returns for remaining member airlines are observed.